Legalizing up to 2 Million Venezuelans—Is Colombia Leading the Way into a More Migration-friendly Future? - Sofia Eigner; Simon Meemken; Bennet Niederhöfer; Britta Rude (CESifo Forum, 2021)
The Venezuelan refugee crisis is one of the largest in the world. It is the most underfunded diaspora worldwide and stresses the already overstretched social protection systems in developing countries in the Latin American region. Colombia has been the main destination for many, but high poverty levels have made it difficult for the country to absorb the effects. Venezuelans in Colombia face elevated levels of poverty, food insecurity and xenophobia. There are gaps with respect to access to health and education, as well as the labor market and housing compared to the local population. The pandemic has further exacerbated those challenges. The Colombian government has now introduced a measure to legalize those residing in the country. How could this affect the situation of the refugee and host population? We give an overview of the situation of Venezuelans in the country and draw from the economic literature to shed some light on the potential implications of the legalization.
Keywords: 330